The Nature of Teacher Questioning Roles while Supporting Dialogue and Argumentation - Kilpelä, Jonathan (2018)
This study examines discourse in physics classes in Finnish lower secondary schools. The goal of the research is to describe how student argumentation can be supported by a variety of teacher discourse, including different communicative approaches and teacher questioning roles. By describing specific features of successful episodes of student argumentation, the hope is to convey a more concrete image of effective instruction, inspiring further research, professional development, and self-reflection by practicing teachers. The methodology utilized in this study approached discourse from multiple levels, aiming to describe the nature of communicative acts in a broad sense as well as in a more specific, moment-by-moment fashion. Discourse analysis was performed on four recorded lessons taught by two teachers aimed at supporting dialogicity and argumentation. The analysis included evaluating discourse based on the type of communicative approach used by the teacher, the teachers’ questioning roles, and the level of student argumentation. Lastly, microanalysis of excerpts of the transcript was included to offer closer insights into the nature of teacher/student interactions. The results of the study show that teachers use a variety of questioning roles in their discourse, but also suggest that not all questioning roles were equally effective at supporting student argumentation. Including a greater variety of questioning roles including moderator, coach, and participant was effective in supporting high-level student argumentation. Closer analysis revealed specific tactics that teachers use when playing various roles in the classroom. The study implies that teachers can utilize multiple roles in order to support student argumentation.